Advancements in the Engineering Modification of Sucrose Phosphorylase - Shuru Ma; Hongyu Zhang; Tingting Lou; Suying Wang (Crystals)
Sucrose phosphorylase (SPase) is a member of the glycoside hydrolase family 13, catalyzing the reversible phosphorolysis of sucrose to produce α–glucose–1–phosphate and exhibiting transglycosylation activity toward multiple substrates. Its wide substrate specificity enables the synthesis of various glycosides, which are broadly applied in food, cosmetics, and pharmaceuticals. However, the industrial application of SPase is constrained by its poor thermostability and limited transglycosylation activity. Therefore, current research focuses on enhancing the thermostability and transglycosylation activity of SPase through efficient engineering strategies based on its crystal structure and catalytic mechanism. This paper systematically reviews the crystal structure and catalytic mechanism of SPase, outlines the application of protein engineering and immobilization strategies in improving the thermostability of SPase, and analyzes how modifications at key amino acid sites affect the synthesis of typical glycosylation products. It also summarizes the limitations of SPase engineering modification strategies and explores the potential of diversified approaches for SPase modification, highlighting its broad application prospects in industrial production and laying a solid foundation for further advancements in SPase engineering modification and its industrial application.